Genetic variant discovery in a patient suspected with inborn errors of immunity by computational analyses / Chear Chai Teng - Chear , Chai Teng (2022)
The NLR family caspase recruitment domain-containing protein 4 (NLRC4) is involved in mediating innate inflammatory response. Mutations in NLRC4 have been shown to cause autoinflammatory disorder (AID). In this study, a twelve-year-old girl suspected of having AID was investigated. To investigate the causative genetic defect and its structural impact, both experimental and computational methods were performed. Whole-exome sequencing and subsequent Sanger sequencing confirmed a heterozygous missense mutation in NLRC4 (c.1970A>T, p.Q657L). The change in this highly conserved residue was predicted to be damaging by in silico predictions. Increased pro-inflammatory cytokines were also observed in this patient. Yet, the exact molecular mechanism of Q657L mutation causing inflammasome activation remains unclear. Therefore, human full-length NLRC4 structure of the resting and activated state were homology modelled. The Q657L mutant structures of both states were then constructed using computational mutagenesis. All structures were subjected to molecular dynamics (MD) simulations to investigate the structural and dynamics changes of NLRC4 protein due to Q657L mutation. The MD simulation results revealed the mutation leads to conformational and dynamics changes in the resting and activated state. These changes might disrupt the autoinhibitory mechanism required to prevent inflammasome activation in the resting state. In the activated state, the MD simulation results also suggested that the mutant structure might favour oligomerization. Therefore, these findings demonstrated the structural impact of Q657L mutation in the NLRC4 inflammasome activation.